Single-Gene Congenic Strain Reveals the Effect of Zbtb16 on Dexamethasone-Induced Insulin Resistance - Krupková, Michaela; Liška, František; Kazdová, Ludmila; Šedová, Lucie; Kábelová, Adéla; Křenová, Drahomíra; Křen, Vladimír; Šeda, Ondřej (Frontiers in Endocrinology, 2018)
Background Glucocorticoids (GCs) are potent therapeutic agents frequently used for treatment of number of conditions, including hematologic, inflammatory, and allergic diseases. Both their therapeutic and adverse effects display significant interindividual variation, partially attributable to genetic factors. We have previously isolated a seven-gene region of rat chromosome 8 sensitizing to dexamethasone (DEX)-induced dyslipidemia and insulin resistance (IR) of skeletal muscle. Using two newly derived congenic strains, we aimed to investigate the effect of one of the prime candidates for this pharmacogenetic interaction, the Zbtb16 gene. Methods Adult male rats of SHR-Lx.PD5PD-Zbtb16 (n = 9) and SHR-Lx.PD5SHR-Zbtb16 (n = 8) were fed standard diet (STD) and subsequently treated with DEX in drinking water (2.6 µg/ml) for 3 days. The morphometric and metabolic profiles of both strains including oral glucose tolerance test, triacylglycerols (TGs), free fatty acids, insulin, and C-reactive protein levels were assessed before and after the DEX treatment. Insulin sensitivity of skeletal muscle and visceral adipose tissue was determined by incorporation of radioactively labeled glucose. Results The differential segment of SHR-Lx.PD5SHR-Zbtb16 rat strain spans 563 kb and contains six genes: Htr3a, Htr3b, Usp28, Zw10, Tmprss5, and part of Drd2. The SHR-Lx.PD5PD-Zbtb16 minimal congenic strain contains only Zbtb16 gene on SHR genomic background and its differential segment spans 254 kb. Total body weight was significantly increased in SHR-Lx.PD5PD-Zbtb16 strain compared with SHR-Lx.PD5SHR-Zbtb16, however, no differences in the weights of adipose tissue depots were observed. While STD-fed rats of both strains did not show major differences in their metabolic profiles, after DEX treatment the SHR-Lx.PD5PD-Zbtb16 congenic strain showed increased levels of TGs, glucose, and blunted inhibition of lipolysis by insulin. Both basal and insulin-stimulated incorporation of radioactively labeled glucose into skeletal muscle glycogen were significantly reduced in SHR-Lx.PD5PD-Zbtb16 strain, but the insulin sensitivity of adipose tissue was comparable between the two strains. Conclusion The metabolic disturbances including impaired glucose tolerance, dyslipidemia, and IR of skeletal muscle observed after DEX treatment in the congenic SHR-Lx.PD5PD-Zbtb16 reveal the Zbtb16 locus as a possible sensitizing factor for side effects of GC therapy.